If an operation % is commutative it implies that x%y = y%x.

As * is commutative for x*y = xy + 4mx + 2ny, we have:

xy + 4mx + 2ny = yx + 4my + 2nx

=> 4mx + 2ny = 4my + 2nx

=> x(2m - n) +...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

If an operation % is commutative it implies that x%y = y%x.

As * is commutative for x*y = xy + 4mx + 2ny, we have:

xy + 4mx + 2ny = yx + 4my + 2nx

=> 4mx + 2ny = 4my + 2nx

=> x(2m - n) + y(n - 2m) = 0

Equating the coefficients of x and y to 0

=> 2m - n = 0 and n - 2m = 0

=> n = 2m

**We cannot find an exact value for m and n, we can only say that they are related by the relation n = 2m**